Deskripsi Faktor Resiko Diabetus Mellitus Gestasional Di Poli Kandungan RSD Kalisat Jember - Aulia Rahmwati (Jurnal Kesehatan dr. Soebandi, 2019)
Gestational diabetes mellitus is a complication in pregnancy that is still rarely noticed by many. Kalisat hospital is a referral hospital in jember. The factors that influence the occurrence of gestational diabetes mellitus include age, body mass index, a history of diabetes mellitus in the family, a history of having given birth to a baby macrosomia. This study aims to describe the risk factors for gestational diabetes mellitus. The research method used is descriptive by using a cross sectional approach and the sampling technique uses simple random sampling with data management taking primary data using a checklist that has been made by the researcher. The results of the data collection were age <35 years (67.4%), BMI> 25 (70.4%), no history of gestational diabetes mellitus (90.1%), no history of ever having a macrosomic baby (95.2 %) as a risk factor for gestational diabetes mellitus. So as a pregnant woman, you need to know about the risk of gestational diabetes mellitus and the need for an examination of cadargula in pregnant women.